P‐tau235: a novel biomarker for staging preclinical Alzheimer’s disease - Lantero‐Rodriguez, Juan; Snellman, Anniina; Benedet, Andrea L; Milà‐Alomà, Marta; Camporesi, Elena; Montoliu‐Gaya, Laia; Ashton, Nicholas J; Vrillon, Agathe; Karikari, Thomas K; Gispert, Juan Domingo; Salvadó, Gemma; Shekari, Mahnaz; et al. (EMBO molecular medicine, 2021)
Alzheimer’s disease (AD) is characterised by a long preclinical phase. Although phosphorylated tau (p‐tau) species such as p‐tau217 and p‐tau231 provide accurate detection of early pathological changes, other biomarkers capable of staging disease progression during preclinical AD are still needed. Combining exploratory and targeted mass spectrometry methods in neuropathologically confirmed brain tissue, we observed that p‐tau235 is a prominent feature of AD pathology. In addition, p‐tau235 seemed to be preceded by p‐tau231, in what appeared to be a sequential phosphorylation event. To exploit its biomarker potential in cerebrospinal fluid (CSF), we developed and validated a new p‐tau235 Simoa assay. Using three clinical cohorts, we demonstrated that (i) CSF p‐235 increases early in AD continuum , and (ii) changes in CSF p‐tau235 and p‐tau231 levels during preclinical AD are consistent with the sequential phosphorylation evidence in AD brain. In conclusion, CSF p‐tau235 appears to be not only a highly specific biomarker of AD but also a promising staging biomarker for the preclinical phase. Thus, it could prove useful tracking disease progression and help enriching clinical trial recruitment. SYNOPSIS A combination of mass spectrometry analysis of brain tissue and ultrasensitive immunoassays in three independent CSF cohorts identifies p‐tau235 as a novel biomarker for Alzheimer's disease (AD) – from preclinical stages to dementia. P‐tau235 appears to be a predominant feature of AD pathology in brain tissue seemingly preceded by p‐tau231. CSF p‐tau235 identifies symptomatic AD with similar accuracy to that of CSF p‐tau231 and p‐tau217. CSF p‐tau235 increases early during preclinical AD, when only subtle changes in amyloid‐β are detectable in CSF. Changes in CSF p‐tau231 and p‐tau235 levels during preclinical AD are consistent with the sequential phosphorylation events in AD brain and can be used as staging biomarkers for the preclinical phase. Graphical Abstract A combination of mass spectrometry analysis of brain tissue and ultrasensitive immunoassays in three independent CSF cohorts identifies p‐tau235 as a novel biomarker for Alzheimer's disease (AD) – from preclinical stages to dementia.